Inspiratory muscle resistance combined with strength training: effects on aerobic capacity in artistic swimmers - Fan, Yuncai; Duan, Yucheng; Gao, Zhiqing; Liu, Yong (Frontiers in Sports and Active Living, 2024)
Objective: This study aimed to investigate the effects of combining inspiratory muscle resistance with strength training on lung function and aerobic capacity in artistic swimmers.Methods:This research constitutes a placebo-controlled randomized trial, involving a five-week walking program conducted twice a week. Fourteen female artistic swimmers were randomly assigned to either the experimental group (TG group, n=7) or the control group (CG group, n=7). Both groups underwent the same strength training program. The TG group performed inspiratory muscle strengthening at 50% of maximum inspiratory pressure (MIP) during strength training, whereas the CG group engaged in strength training with 15% MIP inspiratory muscle training twice a week. Pre- and post-intervention assessments included an incremental stress test, pulmonary function test, inspiratory muscle strength test, and a specialized performance test.Results: Following the 5-week intervention, within-group comparisons revealed that the inspiratory muscle strength index, vital capacity, and forced vital capacity significantly increased in both the CG and TG groups (P<0.01). The TG group exhibited a significant increase in minute ventilation (P<0.05), while the CG group showed a significant increase in tidal volume (P<0.05). Additionally, the TG group demonstrated a significant improvement in running speed at the ventilation threshold and maximum oxygen uptake (P<0.05), along with a significant increase in tidal volume (P<0.01). Both the CG and TG groups showed significant increases in the scores for the 50-meter diving and 25-meter torpedo (P<0.05). Between-group comparisons showed that the TG group experienced significant improvements in the inspiratory muscle strength index, minute ventilation, running speed corresponding to maximum oxygen uptake, and 25-meter torpedo performance (P<0.05).Conclusion: The findings suggest that a 5-week program combining inspiratory muscle resistance with strength training can effectively enhance the aerobic exercise capacity of artistic swimmers. Moreover, high-intensity inspiratory muscle resistance combined with strength training can improve the muscle's ability to utilize oxygen during exercise.